The miRNAs and their regulatory networks responsible for pollen abortion in Ogura-CMS Chinese cabbage revealed by high-throughput sequencing of miRNAs, degradomes, and transcriptomes - Wei, Xiaochun; Zhang, Xiaohui; Yao, Qiuju; Yuan, Yuxiang; Li, Xixiang; Wei, Fang; Zhao, Yanyan; Zhang, Qiang; Wang, Zhiyong; Jiang, Wusheng; Zhang, Xiaowei (Frontiers in Plant Science, 2015)
Chinese cabbage (Brassica rapa ssp. pekinensis) is one of the most important vegetables in Asia and is cultivated across the world. Ogura-type cytoplasmic male sterility (Ogura-CMS) has been widely used in the hybrid breeding industry for Chinese cabbage and many other cruciferous vegetables. Although, the cause of Ogura-CMS has been localized to the orf138 locus in the mitochondrial genome, however, the mechanism by which nuclear genes respond to the mutation of the mitochondrial orf138 locus is unclear. In this study, a series of whole genome small RNA, degradome and transcriptome analyses were performed on both Ogura-CMS and its maintainer Chinese cabbage buds using deep sequencing technology. A total of 289 known miRNAs derived from 69 families (including 23 new families first reported in B. rapa) and 426 novel miRNAs were identified. Among these novel miRNAs, both 3-p and 5-p miRNAs were detected on the hairpin arms of 138 precursors. Ten known and 49 novel miRNAs were down-regulated, while one known and 27 novel miRNAs were up-regulated in Ogura-CMS buds compared to the fertile plants. Using degradome analysis, a total of 376 mRNAs were identified as targets of 30 known miRNA families and 100 novel miRNAs. A large fraction of the targets were annotated as reproductive development related. Our transcriptome profiling revealed that the expression of the targets was finely tuned by the miRNAs. Two novel miRNAs were identified that were specifically highly expressed in Ogura-CMS buds and sufficiently suppressed two pollen development essential genes: sucrose transporter SUC1 and H+-ATPase 6. These findings provide clues for the contribution of a potential miRNA regulatory network to bud development and pollen engenderation. This study contributes new insights to the communication between the mitochondria and chromosome and takes one step toward filling the gap in the regulatory network from the orf138 locus to pollen abortion in Ogura-CMS plants from a miRNA perspective.